On the Hong Kong Chinese Subtitling of English Swearwords - Chen, Chapman (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe objectives of this article are to illustrate how American English swearwords are under-translated in Hong Kong; to explain why English swearwords are inadequately translated in Hong Kong in terms of patronage, illocutionary strategies, and socio-linguistics; to advocate the adoption of Cantonese dynamic equivalents in subtitling English-speaking movies, in particular, American swearwords; to suggest Cantonese dynamic equivalents for American swearwords in Chinese subtitling; and to emphasize the need to pay attention to linguistic, psychosexual, and religious differences between Chinese and Western cultures when subtitling American swearwords.